Analisis Tingkat Kesehatan Bank Syariah Menggunakan Rasio Permodalan, Profitabilitas, Pembiayaan, dan Risiko Kredit - Slamet Santosa; Muhammad Tho'in; Sumadi Sumadi (Jurnal Ilmiah Ekonomi Islam, 2020)
The aims of the research is to find out the soundness level of Islamic banks seen from the capital ratio, profitability, financing, and credit. Islamic banking financial institutions which are to be the focus of this research are Bank Syariah Mandiri (BSM). This research uses quantitative descriptive methods. The data used are the 2014-2018 financial statements. The results of this study indicate that Bank Syariah Mandiri in terms of capital using the CAR ratio shows an average CAR ratio of 14.75%. This means that BSM in terms of capital is ranked very well. Bank Syariah Mandiri in terms of profitability using the ROA and ROE ratio shows an average ROA of 0.53% and ROE of 6%. This means that BSM's ability to generate profits is ranked quite well. Bank Syariah Mandiri in terms of financing using the FDR ratio shows an average FDR ratio of 79.81%. This means that BSM's ability to repay short-term loans and meet agreed financing is at a healthy rating. Bank Syariah Mandiri in terms of credit risk using the NPF ratio shows an average NPF ratio of 3.18%. This means that there is very little credit provided by BSM and the bank is viewed from the aspect of credit risk, including in a good rating. From the results of these research, indicate that the the soundness level of Bank Syariah Mandiri is in a good level of soundness.